Multimodal indicators of non-functional overreaching in NCAA Division I American football athletes: evidence for role-specific physiological adaptation - Aychman, M. M.; Vinson, K.; Tasnim, N.; Perez, J.; Hodes, G. E.; Basso, J. C. (Frontiers in Physiology, 2026)
Introduction: The purpose of this study was to characterize longitudinal patterns associated with non-functional overreaching (NFOR) in NCAA Division I American football athletes across a competitive season using salivary biomarkers, neuromuscular performance measures, and recovery metrics, with exploratory analyses by team role.